2005
DOI: 10.1249/01.mss.0000152887.87785.be
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antioxidant Treatment Effects on Blood Oxidative Stress after Eccentric Exercise

Abstract: These data suggest that eccentric resistance exercise can increase blood biomarkers of oxidative stress in non-resistance trained females, and this vitamin E, C, and selenium supplementation can attenuate the rise in PC and MDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
2
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 28 publications
5
103
2
9
Order By: Relevance
“…Close et al [39] reported greater increases in CK activity up to 24 hours and increases in oxidative stress up to 72 hours following downhill running at 65% VO 2max as compared to level running and suggested that exercise-induced muscle damage may increase oxidative stress due to the production of reactive oxygen species, which later initiate damaging mechanism. Studies with eccentric resistive exercise confirmed that an increase in oxidative stress following repeated eccentric contraction is associated with simultaneous increase in indices of muscle damage [21,22,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Close et al [39] reported greater increases in CK activity up to 24 hours and increases in oxidative stress up to 72 hours following downhill running at 65% VO 2max as compared to level running and suggested that exercise-induced muscle damage may increase oxidative stress due to the production of reactive oxygen species, which later initiate damaging mechanism. Studies with eccentric resistive exercise confirmed that an increase in oxidative stress following repeated eccentric contraction is associated with simultaneous increase in indices of muscle damage [21,22,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that acute eccentric exercise may produce free radicals not only by an enhanced rate of oxygen utilization but also by anaerobic metabolism and secondary inflammation due to the phagocytic activity of immune cells [14,21,22]. Activated neutrophils and macrophages infiltrate damaged muscle, which may be beneficial to muscle repair [23,24]; however, it may also trigger further inflammatory processes and additional muscle damage, in part through an enhanced formation of uncontrolled free radical reactivity in the vicinity of phagocytic activity [25][26].…”
mentioning
confidence: 99%
“…We recently reported in highly trained runners a decrease in antioxidant parameters after repetition of oxidative stimuli (intense hypoxic exercises) during 6 weeks (Pialoux et al, 2006). In this context, an antioxidant supplementation during intense training could maintain physiological antioxidant values and limit ROS damages induced by physical exercise (Schroder et al, 2000;Goldfarb et al, 2005;Morillas-Ruiz et al, 2006). However, the efficiency of antioxidant on the cellular protection against ROS has not yet been fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Οι περισσότερες εργασίες ωστόσο, αναφέρουν σημαντικά υψηλότερες συγκεντρώσεις υπεροξείδωσης λιπιδίων (Childs, Jacobs, Kaminski, Halliwell, & Leeuwenburgh, 2001;Close, et al, 2006;Close, et al, 2004;Close, Ashton, Cable, et al, 2005;Maughan, et al, 1989;Nikolaidis, et al, 2007;Paschalis, et al, 2007;Paschalis, Nikolaidis, et al, 2010a) σε ένα τουλάχιστον χρονικό σημείο μετά την άσκηση. Σημαντικό στοιχείο που προέκυψε από αυτές τις εργασίες είναι ότι δεν είχε αναφερθεί καμία επίδραση της έκκεντρης άσκησης στην λιπιδική υπεροξείδωση τις πρώτες ώρες μετά το τέλος της άσκησης (Cannon, et al, 1990;Close, et al, 2004;Close, Ashton, Cable, et al, 2005c;Goldfarb, et al, 2005;Nikolaidis, et al, 2007;Paschalis, et al, 2007;Paschalis, Nikolaidis, et al, 2010a;Sacheck, et al, 2000;Sacheck, et al, 2003). Από την άλλη οι εργασίες οι οποίες ανέφεραν αλλαγές μετά την άσκηση στην λιπιδική υπεροξείδωση, υποδεικνύουν ότι οι αλλαγές συνέβηκαν χρονικά από την 2 η μέχρι και την 4 η μέρα μετά το τέλος της έκκεντρης άσκησης.…”
Section: έκκεντρη άσκηση και οξειδοαναγωγική κατάσταση του αίματοςunclassified
“…Οι εργασίες που μελέτησαν την επίδραση της λήψης αντιοξειδωτικών βιταμινών C και Ε μεμονωμένα ή συνδυαστικά για περιορισμό της μυϊκής βλάβης και του οξειδωτικού στρες μετά από έκκεντρη άσκηση έχουν να επιδείξουν αντικρουόμενα αποτελέσματα. Οι περισσότερες από αυτές τις εργασίες, όπως φαίνεται συνοπτικά στους Πίνακες 1, 2 και 3, αναφέρουν ότι η λήψη βιταμίνης C και βιταμίνης Ε, συνδυαστικά ή μεμονωμένα, μπορεί να έχει έστω κάποια θετική επίδραση σε κάποιο δείκτη μυϊκής απόδοσης και οξειδωτικού στρες σε κάποια χρονική στιγμή μετά από έκκεντρη άσκηση (Beaton, et al, 2002;Bryer & Goldfarb, 2006;Cannon, et al, 1991;Goldfarb, et al, 2005;Kaminski & Boal, 1992;Phillips, et al, 2003;Sacheck, et al, 2003;Shafat, et al, 2004) . Θα πρέπει ωστόσο να αναφερθεί ότι ενώ αυτές οι εργασίες αναφέρουν θετική επίδραση της λήψης βιταμινών σε ένα δείκτη σε κάποιο χρονικό σημείο, στην ίδια εργασία κάποιος άλλος δείκτης δεν είχε υποστεί καμιά επίδραση από τη λήψη των βιταμινών.…”
Section: Petersen Et Al 2001unclassified